The Effectiveness of Decree of The Minister of Agrarian and Spatial Plan Number 276 Concerning the Appointment of Pakraman Village as The Holder of Land Rights - I Gede Surata; I Gede Arya Wira Sena (International Journal of Social Science and Business, 2022)
The land rights registration before issuing the Decree of the Minister of State for Agrarian Affairs Number 276 of 2017 concerning the appointment of Pakraman Village as the subject of the holder of land rights has yet to be completed and based on the Decree. All druwen Village lands can be registered on a cadastral basis to obtain evidence rights called certificates without harming village manners which, before this decree was issued, had utilized/used the druwen village lands. The problem is balancing control and ownership of land rights belonging to Pakraman Village to create an even distribution of land tenure by Krama Desa. This study uses a type of empirical legal research with descriptive-analytical research. The approach used is a sociological approach, with the types of data: primary and secondary data, data sources are field and library data sources, and the research location is in Buleleng District, Buleleng Regency. The registration of druwen village lands in the Buleleng sub-district, Buleleng Regency, has been carried out completely. However, some villages have yet to be registered because the village druwen lands are controlled by village krama in groups called krama dadia. The rest have effectively implemented the Decree of the Ministry of Agrarian Affairs Number 276 of 2017 in Buleleng District, Buleleng Regency.